THE EFFECTS OF JOB ROTATION PRACTICES ON EMPLOYEE PERFORMANCE: A RESEARCH ON JUNIOR MANAGERS, SENIOR OPERATION AND OPERATION STAFF AT THE DEFENSE MANUFACTURING INDUSTRY IN INDONESIA - Sherliana Jasmine; Trisa Nur Kania (JEES: Journal of Economic Empowerment Strategy, 2022)
The importance of the defense manufacturing industry for national integrity necessitates is inextricably inseparable from the critical role of employees in maintaining the output produced by the system, depicted through employee work performance, particularly in the Operations Division. Job rotation is widely included to maintain a high level of employee performance to deliver their utmost. This study aims to identify and analyse the effect of job rotation on employee performance; non-recursive influence between job rotation and employee performance of the operational division at a defense manufacturing industry in Indonesia, characterized by a downturn in employee performance. The method used in this study are Simple Linear Regression and Structural Equation Modelling (SEM) method to describe the relationship between the observed variables (indicators) and latent variables. The research technique used through library research and field research, including non-participant observation, interviews, and questionnaires using a stratified random sampling technique distributed to 133 respondents as Junior Manager, Senior Operation, and Operation Staff across seven divisions. The results showed that the job rotation variable had a positive and significant effect on employee performance. Job rotation is proposed to be improved, emphasizing skills development to increase employee performance, especially regarding the quality of work indicator.